2004
DOI: 10.1038/nature02266
|View full text |Cite
|
Sign up to set email alerts
|

Whisker movements evoked by stimulation of single pyramidal cells in rat motor cortex

Abstract: Neuronal activity in the motor cortex is understood to be correlated with movements, but the impact of action potentials (APs) in single cortical neurons on the generation of movement has not been fully determined. Here we show that trains of APs in single pyramidal cells of rat motor cortex can evoke long sequences of small whisker movements. For layer-5 pyramids, we find that evoked rhythmic movements have a constant phase relative to the AP train, indicating that single layer-5 pyramids can reset the rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
275
2
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(296 citation statements)
references
References 39 publications
17
275
2
2
Order By: Relevance
“…However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…However, it has also been shown that to a lesser extent, OO activation can occur following direct stimulation of M1 (Woolsey et al, 1979;Benecke et al, 1988;Cruccu et al, 1990;Roedel et al, 2001;Sohn et al, 2004;Paradiso et al, 2005) and deficits transpire in OO function following damage to M1 that are less notable than perioral deficits, but are nonetheless detectable (Kojima et al, 1997). Collectively this observation may contribute to the complex nature of facial expression and possibly add to the inherent difficulties in isolating distinct, individuated facial muscle contractions following cortical stimulation (Woolsey et al, 1952;Strick and Preston, 1979;McGuinness et al, 1980;Brecht et al, 2004;Schieber, 2004).…”
Section: Intranuclear Localization Of Oo Motor Neurons and Implicatiomentioning
confidence: 99%
“…In addition to this nonlinearity caused by spike threshold, other active processes such as dendritic calcium spikes (3)(4)(5) can preferentially amplify synchronous inputs. A variety of ways that timing could impact network function have been explored, including oscillatory synchronization (6,7), strong cascading effects of individual neurons or synapses (8)(9)(10)(11), and information encoding via temporal patterns (12). In the songbird, for example, song neurons receive precisely timed coincident input that recruits active calcium conductances, generating strong, reliable spike bursts that control the song (13,14).…”
mentioning
confidence: 99%
“…Experimental evidence for sparse coding has been found in a range of experimental preparations, including the visual (Baddeley et al, 1997;Vinje and Gallant, 2000), motor (Brecht et al, 2004), barrel (Margrie et al, 2002) and olfactory systems (Perez-Orive et al, 2002;Rinberg et al, 2006;Szyszka et al, 2005), the zebra finch auditory system (Hahnloser et al, 2002), and cat LGN (Dan et al, 1996).…”
Section: Sparse Representations In Cortexmentioning
confidence: 99%
“…At the other extreme, the neural representation could be sparse, at any moment in time engaging only a small fraction of neurons, each highly selective with a narrow receptive field. Although a dense code under some conditions makes the most efficient use of the "representational bandwidth" (DeWeese et al, 2005) available in a neuronal population-why should a large fraction of neurons remain silent most of the time?-sparse models have recently gained support on both theoretical (Asari et al, 2006;Olshausen and Field, 2004;Smith and Lewicki, 2006) and experimental (Baddeley et al, 1997;Brecht et al, 2004;Dan et al, 1996;Hahnloser et al, 2002;Margrie et al, 2002;Szyszka et al, 2005;Vinje and Gallant, 2000) grounds. However, it is not at present clear which of these is a better model of sensory representations in the auditory cortex.…”
Section: Sparse Representation Of Sounds In Auditory Cortex Of Unanesmentioning
confidence: 99%
See 1 more Smart Citation